Unicorns don't give sleigh rides - Dadey, Debbie; Jones, Marcia Thornton; Gurney, John Steven, 1962- (New York : Scholastic, 1997)
The Bailey School kids learn a lesson about the Christmas spirit when they set out to discover if Mr. Withers, the owner of Bailey Stables, is hiding a magical unicorn.
"A Little Apple paperback."
3.5
3-6
Keywords: Bailey School Kids (Fictitious characters) -- Fiction; Unicorns -- Fiction; Animal shelters -- Fiction; Christmas -- Fiction; Bailey School Kids (Fictitious characters) -- Fiction; Unicorns -- Fiction; Animal shelters -- Fiction; Christmas -- Fiction